Iman Dalam Diri Seorang Perwira Di Kapernaum Pada Matius 8 : 10 Serta Relevansinya Bagi Orang Kristen Masa Kini. - Jeicca Melati Siregar; Immanuel Lumbantoruan; Jefri Ade Nasution (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Believing in every struggle we face today is something worth paying attention to. Recently we have seen many suicides occurring. In this case, we can assess a person's attitude in facing struggles, quite a few people now take shortcuts in dealing with problems, whereas we should be able to hope in God, no matter what problems occur in our lives. We can see a good example from the faith of a centurion in believing that Jesus would provide healing. Worldly problems can be answered by the great and extraordinary faith of this officer, who will be an example for today's congregation, so that they do not give up in facing every problem in their lives.